Study of closed-tube Cd diffusion in InSb for mid-IR detector-based applications - Pourali, E. (Heliyon, 2018)
Diffusion process of Cadmium (Cd) in indium antimonide (InSb), in a closed tube system, was studied using Hall measurement technique. Various experiments are carried out to achieve a suitable and sustainable procedure. Process details are reported and discussed in the context. Impurity concentration profiles are modeled using an optimized interstitial-substitutional approach. These Mathematical models are in good agreement with experimental data and can be employed in numerical simulations of InSb-based devices.